A Case Report: Symptomatic Sacral Tarlov Cyst in a Male of 24 Years - Ullah, Quadrat A Eahsan; Hussain, Muhammad Awlad; Sayed, Abu; Quader, Mohammad Abdul (Delta Medical College Journal, 2017)
Perineural (Tarlov) cyst, a rare but benign condition, is meningeal dilatations of the posterior spinal nerve root sheath that most often affects sacral roots and can cause a progressive painful radiculopathy. Tarlov cysts are most commonly diagnosed by lumbosacral magnetic resonance imaging (MRI) and can often be demonstrated by computerized tomography (CT) to communicate with the spinal subarachnoid space. The cyst can enlarge via a net inflow of cerebrospinal fluid, eventually causing symptoms by distorting, compressing, or stretching adjacent nerve roots. It is generally agreed that asymptomatic Tarlov cysts do not require treatment. When symptomatic, the potential surgery-related benefit and the specific surgical intervention remain controversial. A 24 years old male presented with a history of trauma and pain in his low back with dull headache for six months. Physical and radiographic examination was consistent with tarlov cyst. Microsurgical excision with plication of the cyst wall was performed. Histo-pathological examination confirmed the diagnosis of Tarlov cyst. Excellent clinical and functional results were obtained with no recurrence after 6 months of follow-up. Tarlov cyst in a male of age 24 is a rare entity and decision making for management poses difficulties. Our experience with microsurgical excision with plication of the cyst wall was quite satisfactory with excellent clinical result, and we recommend this as one of the satisfactory modalities of treatment of Tarlov cyst in adult. Delta Med Col J. Jul 2017 5(2): 99-103